The Role of the Leadership Function in Improving Employee Performance in Correctional Institutions in Indonesia - denny nazaria rifani; Iqbal Saputra Zana; Markus Marselinus Soge (Jurnal Paradigma (JP), 2021)
In achieving constitution of Number 12 of 1995 concerning Correctional, the smooth operation of prisons is very dependent on existing human resources and the resulting performance, namely the performance of correctional officers including prison leaders. This study examines the importance of the role of the leadership function in improving employee performance, especially in prisons in Indonesia. With the aim of analyzing how big the role of the leadership function is to improve employee performance. This research is a type of qualitative research, the research method is carried out by studying the literature. The results of this study require the role of a leader who has the ability and expertise to provide good direction and communication to employees with the role of a leadership function.Keywords: Leadership Functions; Correctional Institutions.